COPD and T2DM: a Mendelian randomization study - Wang, Tao; Li, Jinshuai; Huang, Chun; Wu, Xiangjian; Fu, Xiaoyan; Yang, Chunfeng; Li, Minfang; Chen, Sheng (Frontiers in Endocrinology, 2024)
presents a comprehensive Mendelian randomization analysis investigating the causal relationship between Chronic Obstructive Pulmonary Disease (COPD) and Type 2 diabetes (T2DM). The study utilizes large-scale genetic datasets to establish and quantify the causal effect of COPD on T2DM, shedding light on the underlying mechanisms. This research contributes to both the fields of respiratory and endocrine diseases, providing valuable insights for clinicians managing patients with these co-diagnosed conditions. Given its focus on uncovering the causal dynamics between two prevalent chronic diseases, our manuscript aligns well with the scope of the Journal of Diabetes and Metabolism, offering crucial findings that can inform treatment and prevention strategies